2022
DOI: 10.3390/su14052991
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Profit Efficiency for Spinach Production under Small-Scale Irrigated Agriculture in the Eastern Cape Province, South Africa

Abstract: Improving profit efficiency in vegetable farming, especially for Spinach, is vital in enhancing income, livelihoods, and nutrition security and reducing the poverty of smallholder farmers, particularly in developing countries like South Africa. Despite the country’s potential, spinach production faces major challenges, including unreliable markets, low adoption of modern production systems, and production inefficiencies that affect farm returns. This has been attributed to a lack of adequate and reliable infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…This is not surprising given the cultural norms in Africa, where females take care of the family chores while men dominate the outside chores such as farming. These results were in line with Mdoda et al (2022). The average age of participants (45 years) and non-users (48 years) was significant, implying that age is an important variable in the decision-making process for smallholder farming in the study area.…”
Section: Data and Sources Of Datasupporting
confidence: 86%
“…This is not surprising given the cultural norms in Africa, where females take care of the family chores while men dominate the outside chores such as farming. These results were in line with Mdoda et al (2022). The average age of participants (45 years) and non-users (48 years) was significant, implying that age is an important variable in the decision-making process for smallholder farming in the study area.…”
Section: Data and Sources Of Datasupporting
confidence: 86%
“…Farmers with land ranging between 6 and 10 hectares represent 60% of the respondents, and only two have land above 10 hectares. In the Eastern Cape, the average size of productive land is two hectares (Mdoda et al, 2022;von Loeper et al, 2016). A study conducted on smallholder farms in Ethiopia, Ghana, Mali, Malawi, Tanzania and Uganda revealed that the majority of the farms are operated on land less than a hectare (Giller et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This was basically the incentive provided by the families of the respondents, as youths themselves had no funding. This was not surprising, because farmers' access to credit is a challenge in the province [28,29]. Youth had financial support from government (28%) and NGOs (24%).…”
Section: Source Of Funding For Youth Engaged In Agricultural Enterprisesmentioning
confidence: 99%